Równi czy nierówni? O kobiecie i mężczyźnie w ujęciu wybranych autorów pogańskich i wczesnochrześcijańskich - Jachna, Marta (Colloquia Litteraria, 2022)
The article discusses the question of value and role of the two sexes on the basis of the selected writings of the Fathers of the Church (St. John Chrysostom, St. Clement of Alexandria) as well as pagan writers (Plutarch, Seneca the Younger). They consider the issue of dignity of a woman and a man as a human, position in society, and relationship. Authors agree a woman is physically and emotionally weak and she is under the authority of a man. Both sexes still have equal participation in the moral virtue and their role along with duties are equally important although absolutely different.